The Difference in Patient Characteristics based on Cervical Cancer Stage at Soedarso Hospital - Fatinah, Nabilah Nurul; Pratiwi, Sari Eka; Trianto, Heru Fajar; Wahyudi, Tri; Rahmayanti, Sari (Universitas Muhammadiyah Yogyakarta, 2023)
Cervical cancer ranks fourth-most in cancer mortality in women worldwide and second in incidence and mortality from cancer in women in Indonesia. Many cervical cancer patients are diagnosed at an advanced stage with a poor prognosis and increased mortality, so it is necessary to identify the characteristics related to the stage. This research aims to determine the differences in patient characteristics based on the cervical cancer stage. This study was analytical with a cross-sectional approach. Samples were taken using consecutive sampling techniques with a total sample of 99 people. The research was conducted at Soedarso Hospital Pontianak by collecting data from medical records and an anatomical pathology laboratory. Most cervical cancer patients in this study were 41-50 years of age (39,4%), were a housewife (78,8%), had graduated from elementary school (44,4%) and had a number parity of more than 5 (31,3%). The data were analyzed using the Kruskal-Wallis. Statistical tests showed a significant difference between age (p 0.000), occupation (p 0.003), and parity (p 0.017) to the cervical cancer stage. It indicated that older ages, more parity, and housewife tended to be diagnosed with an advanced stage of cervical cancer. This study implied that older women, more parity, and housewives should be more aware of cervical cancer risk.